TDO2 deficiency attenuates the hepatic lipid deposition and liver fibrosis in mice with diet-induced non-alcoholic fatty liver disease - Zhi Qin; Min Zhou (Heliyon, 2023)
Purpose: Non-alcoholic fatty liver disease (NAFLD) represents an increasingly prevalent set of liver diseases. Tryptophan 2,3-dioxygenase 2 (TDO2) is the major enzyme of tryptophan catabolism and is abnormally expressed in liver cancer, but the function of TDO2 in NAFLD remains unclear. The current study was designed to probe into the effect and mechanism of TDO2 on NAFLD. Methods: C57BL/6 mice and TDO2-knockout (KO) mice were fed with a high-fat diet for 16 weeks to construct the NAFLD model in vivo; primary hepatocytes isolated from TDO2-KO mice were exposed to palmitate (PA) to establish the NAFLD model in vitro. The expression of TDO2 was determined using Western blot. The function and mechanism of TDO2 were evaluated by enzyme-linked immunosorbent assay, hematoxylin-eosin staining, Oil Red O staining, immunohistochemical assay, and Western blot. Results: The expression of TDO2 in the liver tissue of NAFLD mice was more than three times that in the control group. Functionally, TDO2 knockout reduced hepatic lipid deposition and liver fibrosis in NAFLD mice in vivo and primary hepatocytes induced by 200 μM PA in vitro. Mechanistically, the loss of TDO2 restrained hepatic lipid deposition and expression levels of fibrosis-related markers in PA-treated primary hepatocytes, and these trends were partially reversed by 10 ng/ml receptor activator of the nuclear factor kappa-B ligand (RANKL, an activator of the NF-κB pathway). Conclusion: Knocking out TDO2 repressed hepatic lipid deposition and liver fibrosis in mice with NAFLD, and reduced hepatic lipid deposition and expressions of fibrosis-related markers in PA-treated primary hepatocytes by inactivating the NF-κB pathway.